Biosorption of macronutrients by Brazilian tropical peats - Melo, Camila Almeida [UNESP]; de Oliveira, Lílian Karla [UNESP]; Fraceto, Leonardo Fernandes [UNESP]; Rosa, André Henrique [UNESP] (Taylor & Francis, 2018)
The objective of this work was to evaluate the adsorption of macronutrients calcium, potassium, magnesium, nitrogen, and phosphorus in two Brazilian tropical peat samples, investigating the effect of pH and determining the kinetics of the adsorption process. Two different Brazilian tropical peat samples were characterized using FTIR, TG, and SEM techniques. Different pH conditions were tested, as well as different mass concentrations of the peats. Differences in the chemical structures of the peat samples directly influenced the adsorptive capacities for the macronutrients. The adsorptive capacity for nitrogen was highest at pH 3, while the best adsorption of calcium and potassium was obtained at pH 6. The best fit to the data was provided by the pseudo-second-order model, which confirmed the rapid adsorption of calcium by both peats.
Keywords: Adsorption; kinetics; macronutrients; tropical peat